2019
DOI: 10.1016/j.clae.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in corneo-scleral topographic profile between healthy and keratoconus corneas

Abstract: The corneo-scleral profile in keratoconus presents higher levels of asymmetry compared to healthy eyes, especially in eyes with moderate and advanced stages of the disease. The diagnostic accuracy of corneo-scleral topographic data alone for keratoconus detection is limited and must be used in conjunction with other clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 27 publications
(56 reference statements)
2
39
0
Order By: Relevance
“…However, it must be noted that when corneal thickness is subtracted from ACD values, that is, when the reference point for measurements is the endothelium, the it may be concluded that the changes produced by the emergence of keratoconus not only affect the corneal portion of the eye, but the entire anterior segment, as previously suggested [6,7]. Indeed, Piñero et al [7], using the recently available corneo-scleral topographer Eye Surface Profiler (Eaglet Eye b.v., Houten, The Netherlands) also reported significant correlations between several corneal and scleral parameters, particularly in those patients presenting more advanced keratoconus. Our findings also…”
Section: Ocular Conditionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it must be noted that when corneal thickness is subtracted from ACD values, that is, when the reference point for measurements is the endothelium, the it may be concluded that the changes produced by the emergence of keratoconus not only affect the corneal portion of the eye, but the entire anterior segment, as previously suggested [6,7]. Indeed, Piñero et al [7], using the recently available corneo-scleral topographer Eye Surface Profiler (Eaglet Eye b.v., Houten, The Netherlands) also reported significant correlations between several corneal and scleral parameters, particularly in those patients presenting more advanced keratoconus. Our findings also…”
Section: Ocular Conditionmentioning
confidence: 96%
“…In addition, Scheimpflug images have been used to measure corneal peripheral angles in healthy and keratoconic eyes in different corneal meridians [6]. The findings of these and similar studies [7,8] suggest that keratoconus is accompanied by central and peripheral corneal involvement and by changes in the scleral shape, adjacent to the limbus. It has also been shown that the evaluation of corneal and anterior segment parameters may be useful for the characterization of the peripheral cornea, the limbal and the near limbus scleral zone, and, therefore, to gain a better understanding of the morphological changes in keratoconus [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 93%
“…The authors also concluded that higher corneal astigmatism (>2.00D) could be associated with scleral toricity. Other studies found that the scleral topography of irregular and regular shaped corneas have differences, which could have a direct impact on SL fitting, namely when choosing the best landing zone geometry for the different eyes [2628].…”
Section: Discussionmentioning
confidence: 99%
“…Although SL are very stable on-eye, they tend to decenter. e geometric characteristics of the ocular surface beyond the corneal borders (flatter sclera in the nasal side), gravity, and eyelids effect usually make the SL to decenter inferotemporally [24][25][26][27][28][29]. However, some manufacturers are able to overcome this issue by decentering the optic zone to compensate for this misalignment with the visual axis, which could be very beneficial for presbyopic and myopia control designs.…”
Section: Platforms For Bifocality and Multifocality In Contact Lensesmentioning
confidence: 99%